ANALISIS KONTRASTIF IDIOM BAHASA JEPANG KI DAN IDIOM BAHASA INDONESIA "HATI" : KAJIAN LINGUISTIK KOGNITIF - Dany Buyung Yudha Prasetya, - (2019)
This study trying to describe the relationship between lexical meaning and the idiomatical meaning of 'ki' in the Japanese language idioms and 'hati'in Indonesian language Idiom by using cognitive linguistic as the perspectives. This study classified as a basic research category, because this research was conducted to find new theories about how idioms get to motivated from the relationship between lexical meaning and idiomatic meaning in the cognitive linguistics point of view, finds differences and similarities between Japanese and Indonesian idioms. Then contrasted the idioms using the matching techniques of linguistics. From the results of the analysis it can be seen that even though there are idioms that have the same lexical meaning but almost all of them have different idiomatic meanings due to different points of view, and cultural differences. Then it is reinforced by explanations and data that although the lexical meaning between the two idioms is different, due to the almost similarity of perspectives, it results in idiomatical equations or similarity in idioms of both languages. ki idiom, hati idiom, cognitive linguistics, contrastive analysis, japanese language education